THU0253 In Early Undifferentiated Arthritis Autoantibodies and Power Doppler Identify Patients Achieving Remission after 12 Months of Treatment. (10th June 2014) - Sakellariou, G.; Scirè, C.A.; Balduzzi, S.; Fusetti, C.; Caporali, R.; Montecucco, C.
Abstract : Background: As a consequence of the 2010 classification criteria for rheumatoid arthritis (RA) the definition of undifferentiated arthritis (UA) has changed, identifying different clinical patterns (1). Ultrasonographic (US) features and predictors of response in this population have not been described yet. Objectives: To evaluate the clinical and US features in patients with UA according to the 2010 criteria, the occurrence of clinical remission in the first 12 months of treatment and its clinical and US predictors. Methods: Patients attending an early arthritis clinic (2005-2012) with a 2010 classification criteria score <6 were included, after the exclusion of other causes of arthritis. US of bilateral wrists and metacarpophalangeal joints (1-5) was performed at baseline to detect synovitis by gray scale (GS) and power Doppler (PD). GS and PD were graded 0-3 in each joint, overall scores were obtained as the sum of single joints. Patients seen before October 2010 were classified according to the 1987 criteria, while the 2010 criteria were applied afterwards: patients with RA received methotrexate (MTX), while UA patients hydroxychloroquine (HCQ). Low-dose prednisone could be given based on clinical judgment. Patients were seen every 2 months in the first 6 months and every 3 afterwards and treatment adjusted to reach a DAS28<3.2. Clinical remission (DAS28<2.6) in the first 12 months was evaluated as outcome. The effect of clinical variables, single items of the 2010 classification score and US variables on the achievement of clinical remission was evaluated through Cox regression analysis and results presented as Hazard Ratios (HR, 95% CI), adjusted for age, gender, glucocorticoids and the use of DMARDs (excluding HCQ) over time. Results: A total of 215 patients were included. Median (IQR) follow-up was 12 (6-12) months, mean (sd) age 56.8 years (15.07), 64 patients (29.7%) were male, mean DAS28 was 3.74 (0.95). The median score of the 2010 criteria was 4 (4-5). At baseline HCQ was given to 169 (78.6%) patients and prednisone to 87 (40.5%). The median GS and PD scores were 4 (2-17) and 1 (0-14), respectively. Within the first year of observation 124 (57.7%) patients achieved clinical remission at least once. Remission was less likely in older (HR 0.98 (0.97, 0.99)p=0.014) and female (HR 0.64 (0.45, 0.90), p=0.012) patients. High titers of anti-citrullinated peptide antibodies and/or rheumatoid factor predicted remission (HR 3.34 (1.30, 8.57) p=0.012), while the remaining items of the criteria did not. Among US variables, a baseline PD score>0 (HR 1.75 (1.06, 2.88) p=0.027) or a PD score>1 (HR 1.68 (1.03, 2.72) p=0.036), the presence of at least one joint with PD>1 (HR 1.81 (1.07, 3.06), the count of joints with PD>0 (HR 1.15 (1.03, 1.28) p=0.012) and PD>1 (HR 1.30 (1.05, 1.61)) and the overall PD score (HR1.10 (1.02, 1.18) p=0.011) predicted subsequent clinical remission. Conclusions: High-titer autoantibodies (2) and PD identify UA patients that are more likely to reach clinical remission when treated. These features might be useful to drive the decision to start treatment in early UA. References: Krabben A, et al. Ann Rheum Dis 2012;71:238-41. Wevers-de Boer K, et al. Ann Rheum Dis 2012;71:1472-7. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5046